Foramen of Winslow hernia years after a Ladd's procedure: A case report. (2020) - Abu-Swis, Shadi; Cohen, Nir; Wallach, Nadav; Abo-Sharb, Adam; Sebbag, Gilbert; Kian, Waleed
Abstract: Foramen of Winslow hernias form 8% of all internal hernias. They present with non-specific findings and are often diagnosed late in disease progression. Delayed diagnosis of the hernia is associated with an estimated mortality of 50%. This rare event has yet to be described in the literature as a follow-up complication to a Ladd's procedure. Here, we present a young male patient with a surgical history of a Ladd's procedure with a chief complaint of an acute-onset, severe abdominal pain accompanied by episodes of emesis. Prompt clinical analysis, imaging and fluid resuscitation was conducted. A computed tomography (CT) scan showed a mesenteroaxial gastric volvulus and air was identified within the Falciform Ligament. Consequently, the patient underwent an exploratory laparotomy and the foramen of Winslow hernia was identified. An excision and anastomosis procedure was performed, and the cecum was fixed in the lower left quadrant. The procedure had no complications and the patient was discharged from the hospital on the fifth post-operative day. The purpose of this case report is to present an unusual patient who experienced a foramen of Winslow hernia involving the small bowel six years following a Ladd's procedure. While a causative relation cannot be made between these two events, we theorize that gastrointestinal hypermobility, being one of the three properties leading to herniation, played a role in both pathologies. Therefore, a vigilant surgeon should keep in mind that intra-abdominal congenital malrotation can put patients at greater risk for future herniation.